Medicine inventory control by considering expiry periods and product returns using the Always Better Control (ABC) analysis and the handley within model of Economic Order Quality (EOQ) at pharmacies in Indonesia - Sukendar, Irwan; Sugiyono, Andre; Monfiqotusshifa, Monfiqotusshifa (UUM College of Business, 2020)
This study aims to control medicine inventories by considering the expiration period and the product return using The Always Better Control (ABC) analysis and The handley within model of Economic Order Quantity (EOQ). The results of this study indicate that there are 21% of medicines or 22 types of medicines belonging to group A with the use of 74.64%. for group B there were 25% drugs or 28 types of drugs with a budget use of 15.31% of all medicines. Meanwhile, there are 55% of medicines or 60 types of medicines belonging to group C with the use of a budget of 10.05% of the total medicines and the calculation using the EOQ method by considering the expiration period and product returns in this research has a more optimal order size compared to the previous method so that it can minimize expired medicines and estimate which medicines will expire at the end of the cycle so that the total cost of supplies at the pharmacy is more optimal.